The child and adolescent athlete: a review of three potentially serious injuries - Caine, D.; Purcell, L.; Maffulli, N. (BMC Sports Science, Medicine and Rehabilitation, 2014)
The increased participation of children and adolescents in organized sports worldwide is a welcome trend given evidence of lower physical fitness and increased prevalence of overweight in this population. However, the increased sports activity of children from an early age and continued through the years of growth, against a background of their unique vulnerability to injury, gives rise to concern about the risk and severity of injury. Three types of injury - anterior cruciate ligament (ACL) injury, concussion, and physeal injury - are considered potentially serious given their frequency, potential for adverse long-term health outcomes, and escalating healthcare costs. Concussion is probably the hottest topic in sports injury currently with voracious media coverage and exploding research interest. Given the negative cognitive effects of concussion, it has the potential to have a great impact on children and adolescents during their formative years and potentially impair school achievement and, if concussion management is not managed appropriately, there can be long term negative impact on cognitive development and ability to resume sports participation. Sudden and gradual onset physeal injury is a unique injury to the pediatric population which can adversely affect growth if not managed correctly. Although data are lacking, the frequency of stress-related physeal injury appears to be increasing. If mismanaged, physeal injuries can also lead to long-term complications which could negatively affect ability to participate in sports. Management of ACL injuries is an area of controversy and if not managed appropriately, can affect long-term growth and recovery as well as the ability to participate in sports. This article considers the young athlete's vulnerability to injury, with special reference to ACL injury, concussion, and physeal injury, and reviews current research on epidemiology, diagnosis, treatment, and prevention of these injury types. This article is intended as an overview of these injury types for medical students, healthcare professionals and researchers.